2017
DOI: 10.1016/j.stemcr.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

2i Maintains a Naive Ground State in ESCs through Two Distinct Epigenetic Mechanisms

Abstract: SummaryMouse embryonic stem cells (ESCs) are maintained in serum with leukemia inhibitory factor (LIF) to maintain self-renewal and pluripotency. Recently, a 2i culture method was reported using a combination of MEK inhibition (MEKi) and GSK3 inhibition (GSK3i) with LIF to maintain ESCs in a naive ground state. How 2i maintains a ground state of ESCs remains elusive. Here we show that MEKi and GSK3i maintain the ESC ground state by downregulating global DNA methylation through two distinct mechanisms. MEK1 pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 77 publications
(121 reference statements)
4
49
0
Order By: Relevance
“…Naïve pluripotent ES cells cultured in LIF/2i are thought to maintain a more balanced and stable state than ES cells maintained in LIF/serum through higher and more uniform expression of the major pluripotency transcription factors in the cell population (Tosolini and Jouneau 2016;Sim et al 2017). Our results indicate that for KLF4 protein, this higher and more uniform expression in LIF/2i is achieved through posttranslational protein stabilization.…”
Section: Klf4 Protein Stability Is Modulated In Es Cellsmentioning
confidence: 70%
“…Naïve pluripotent ES cells cultured in LIF/2i are thought to maintain a more balanced and stable state than ES cells maintained in LIF/serum through higher and more uniform expression of the major pluripotency transcription factors in the cell population (Tosolini and Jouneau 2016;Sim et al 2017). Our results indicate that for KLF4 protein, this higher and more uniform expression in LIF/2i is achieved through posttranslational protein stabilization.…”
Section: Klf4 Protein Stability Is Modulated In Es Cellsmentioning
confidence: 70%
“…We, however, showed that Zfp281 drives exit from naïve pluripotency independent of Dnmt3a, Dnmt3b, Tet1, and Tet2. Although the specific contributions of 5-methylcytosine, H3K9me2, and other Ehmt substrates (Sim et al, 2017) to pluripotent cell plasticity remain to be determined, our findings suggest that resolution of naïve pluripotency in vitro is masked or mechanistically distinct in heterogeneous Serum/Lif ESC cultures. Similarly, Zic2 has previously been reported to act as a repressor in metastable serum/Lif ESCs (Luo et al, 2015), but we detect only minor transcriptional defects in naïve Zic2 KO ESCs.…”
mentioning
confidence: 83%
“…Nevertheless, 38% of target genes were downregulated. Changes in the absence of Ehmt1 are therefore likely consequential to both direct and indirect effects and may also include the contribution of non-histone Ehmt1 substrates (Sim et al, 2017) to transcription. Based on mRNA levels, Zic2 32 h cells were not separated from matching control cells ( Fig 6A-D).…”
Section: Overlapping Transcriptional Functions Of Zfp281 and Ehmt1/zic2mentioning
confidence: 99%
“…Embryonic stem cells are known to exhibit dramatic changes in morphology and mechanics during the first few days after fertilization. Cultured ESCs can be maintained in a ground state of totipotency or pluripotency by maintaining certain culture conditions and their exact stage can be detected by associated expression levels of transcription factors (9,10). Cells cultured in serumfree media with the addition of two small molecule inhibitors of GSK3 and MEK along with leukemia inhibitory factor (LIF) resemble the 3.5 day post fertilization (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Cells cultured in serumfree media with the addition of two small molecule inhibitors of GSK3 and MEK along with leukemia inhibitory factor (LIF) resemble the 3.5 day post fertilization (11)(12)(13). These cells exhibit a greater level of pluripotency than cells grown in serum media supplemented with LIF (9,13,14) and exhibit a remarkably different morphology when grown on a substrate. To our knowledge, no study has quantitatively investigated the structural and physical properties of cells cultured in these two widely used culture conditions.…”
Section: Introductionmentioning
confidence: 99%